Pedagoška praksa z vidika empirično verificirane ocene visokošolskih didaktikov - Čagran, Branka (Sodobna pedagogika, 2007)
In the introduction to this paper, the authors first describe some paradigmatic changes in teacher education in the modern world, and specifically the new role of teaching practice in teacher education programmes. The main part of the paper presents the findings of a case study implemented in the 2004/2005 academic year, which aimed to investigate the current teaching practice at the Faculty of Education at the University of Maribor, as viewed by university-based teacher-educators according to their experience, expectations and proposals for changes. The data were collected by means of a questionnaire containing previously validated measurement characteristics and processed at the level of descriptive and inferential statistics. The obtained empirical results show the need for measures aimed at the renewal of teaching practice. The findings of the case study call for the renewal of teaching practice in accordance with the modern, reflective model of teacher education.
Keywords: učitelji; izobraževanje učiteljev; strokovna usposobljenost; pedagoška praksa